Implementation of Bela Negara Strengthening Program and Maritime at NALA East Java State High School Malang - Sulistiyanto,; Suprapto,; Sudarya, Agus (Advances in Social Sciences Research Journal, 2022)
The implementation of the program to strengthen the values ​​of bela negara and maritime affairs is very necessary for the younger generation in welcoming the future development of the beloved nation and state of Indonesia, especially for those who are still studying in high school / high school equivalent. SMANTAR NALA East Java which implements a boarding school has implemented this program since 2017 whose implementation is in collaboration with the Indonesian Navy which uses the 2013 Revised + Senior High School national curriculum. The research used was a qualitative method with the object of research being SMANTAR NALA, Naval Institution for recruitment (LAPETAL) and Naval Academy (AAL) while the subjects were the Principal, special expert of curriculum, Deputy Principal, Teachers teaching related material, representatives of the Indonesian Navy caregiver and student representatives. The results of the research at SMANTAR NALA East Java, there is a significant strengthening of the values ​​of bela negara and maritime affairs which is very much needed for the next generation, especially high school students and it is still possible if applied to non-boarding high school in both public and private schools by modifying the curriculum slightly. Among other things, adding one hour learning of 45 minutes of study every semester so that in the future it is hoped that the sense of nationalism and the spirit of state defence in the younger generation, especially at the senior high school level, can be maintained. Key words: value reinforcement. state defense, maritime, boarding school SMANTAR NALA East Java, senior high school students